A guide to Asperger Syndrome - Gillberg, Christopher (Estados Unidos : Cambridge University, 2003)
This book is intended for all those who struggle with Asperger Syndrome in their eveyday life. The are many. Ther range from the people with the diagnosis and their near and dear, thorough clinicians faced with the problems of understanding.
Contents 1. Introduction 2. Definitions 3. Prevalence 4. Symtoms in childhood 5. Symptoms in adolescence 6. Associated psychiatric and social problems 7. Other problems 8. Strengths 9 Background factors 10. Cognitive neuropsychology
Contiene referencias bibliograficas
Keywords: ASPERGER SYNDROME; SINDROME DE ASPERGER